Stability of Emotional and Behavioral Functioning in Youth with Inflammatory Bowel Disease - Reed-Knight, Bonney (Child Health Care, 2013)
This study prospectively examined stability of psychological and behavioral functioning in two matched cohorts of youth with inflammatory bowel disease (IBD): (1) newly-diagnosed and (2) previously-diagnosed patients. Youth and their parents completed measures of emotional and behavioral functioning at Time 1 and 6-months later. Mean-level analyses indicated that scores at Time 1 and Time 2 were within the nonclinical range. A significant decrease occurred in Internalizing symptoms for previously-diagnosed patients. Both groups demonstrated high levels of profile stability, with no significant differences across groups. Results suggest that emotional and behavioral functioning is generally stable without targeted intervention.